Wireless Vehicular Networks for Car Collision Avoidance - Naja, Rola.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Wireless Vehicular Networks for Car Collision Avoidance focuses on the development of the ITS (Intelligent Transportation Systems) in order to minimize vehicular accidents. The book presents and analyses a range of concrete accident scenarios while examining the causes of vehicular collision and proposing countermeasures based on wireless vehicular networks. The book also describes the vehicular network standards and quality of service mechanisms focusing on improving critical dissemination of safety information. With recommendations on techniques and protocols to consider when improving road safety policies in order to minimize crashes and collision risks.
A Survey of Communications for Intelligent Transportation Systems -- Quality of Service Provisioning in Wireless Vehicular Networks: Challenges and Mechanisms -- Message dissemination in VANET: protocols and performances -- Rear End Collision: Causes and Avoidance Techniques -- Chain Collision Accident: Causes and Avoidance Techniques -- Lane Change and Overtaking Collisions: Causes and Avoidance Techniques -- Intersection Collision: Causes and Avoidance Techniques -- Cars and Pedestrians Collision: Causes and Avoidance Techniques.
Keywords: Engineering; Computer Communication Networks; Telecommunication; Engineering; Communications Engineering, Networks; Computer Communication Networks; Signal, Image and Speech Processing; Automotive Engineering